Loss of B cells and their precursors is the most constant feature of GATA-2 deficiency in childhood myelodysplastic syndrome - Nováková, Michaela; Žaliová, Markéta; Suková, Martina; Wlodarski, Marcin; Janda, Aleš; Froňková, Eva; Campr, Vít; Lejhancová, Kateřina; Zapletal, Ondřej; Pospíšilová, Dagmar; Černá, Zdeňka; Kuhn, Tomáš; et al. (Haematologica, 2016)
GATA-2 deficiency was recently described as common cause of overlapping syndromes of immunodeficiency, lymphedema, familiar myelodysplastic syndrome or acute myeloid leukemia. The aim of our study was to analyze bone marrow and peripheral blood samples of children with myelodysplastic syndrome or aplastic anemia to define prevalence of the GATA2 mutation and to assess whether mutations in GATA-2 transcription factor exhibit specific immunophenotypic features. The prevalence of a GATA2 mutation in a consecutively diagnosed cohort of children was 14% in advanced forms of myelodysplastic syndrome (refractory anemia with excess blasts, refractory anemia with excess blasts in transformation, and myelodysplasia-related acute myeloid leukemia), 17% in refractory cytopenia of childhood, and 0% in aplastic anemia. In GATA-2-deficient cases, we found the most profound B-cell lymphopenia, including its progenitors in blood and bone marrow, which correlated with significantly diminished intronRSS-Kde recombination excision circles in comparison to other myelodysplastic syndrome/aplastic anemia cases. The other typical features of GATA-2 deficiency (monocytopenia and natural killer cell lymphopenia) were less discriminative. In conclusion, we suggest screening for GATA2 mutations in pediatric myelodysplastic syndrome, preferentially in patients with impaired B-cell homeostasis in bone marrow and peripheral blood (low number of progenitors, intronRSS-Kde recombination excision circles and naïve cells).
Keywords: imunofenotypizace; B-lymfocyty; Immunophenotyping; Humans; Bone Marrow Cells; biologické markery; kojenec; Adolescent; Child; Child, Preschool; GATA2 Transcription Factor; počet lymfocytů; Biomarkers; Myelodysplastic Syndromes; Myeloid Cells; T-lymfocyty - podskupiny; Anemia, Aplastic; B-Lymphocytes; Bone Marrow; lidé; Lymphocyte Count; Precursor Cells, B-Lymphoid; Phenotype; myelodysplastické syndromy; Lymphopenia; myeloidní buňky; kostní dřeň; dítě; mutace; mladý dospělý; ROC křivka; T-Lymphocyte Subsets; ROC Curve; Diagnosis, Differential; fenotyp; Mutation; Infant; mladiství; lymfopenie; předškolní dítě; aplastická anemie; buňky kostní dřeně; transkripční faktor GATA2; prekurzorové B-lymfoidní buňky; diferenciální diagnóza; Young Adult